Genome-Wide Identification of CBL-CIPK Gene Family in Honeysuckle (Lonicera japonica Thunb.) and Their Regulated Expression Under Salt Stress - Huang, Luyao; Li, Zhuangzhuang; Fu, Qingxia; Liang, Conglian; Liu, Zhenhua; Liu, Qian; Pu, Gaobin; Li, Jia (Frontiers in Genetics, 2021)
In plants, calcineurin B-like proteins (CBLs) are a unique group of Ca2+ sensors that decode Ca2+ signals by activating a family of plant-specific protein kinases known as CBL-interacting protein kinases (CIPKs). CBL-CIPK gene families and their interacting complexes are involved in regulating plant responses to various environmental stimuli. To gain insight into the functional divergence of CBL-CIPK genes in honeysuckle, a total of 6 LjCBL and 17 LjCIPK genes were identified. The phylogenetic analysis along with the gene structure analysis divided both CBL and CIPK genes into four subgroups and validated by the distribution of conserved protein motifs. The 3-D structure prediction of proteins shown that most LjCBLs shared the same PDB hit 1uhnA and most LjCIPKs shared the 6c9Da. Analysis of cis-acting elements and gene ontology implied that both LjCBL and LjCIPK genes could be involved in hormone signal responsiveness and stress adaptation. Protein-protein interaction prediction suggested that LjCBL4 is hypothesized to interact with LjCIPK7/9/15/16 and SOS1/NHX1. Gene expression analysis in response to salinity stress revealed that LjCBL2/4, LjCIPK1/15/17 under all treatments gradually increased over time until peak expression at 72 h. These results demonstrated the conservation of SOS pathway genes in honeysuckle and a model of Ca2+-LjCBL4/LjSOS3-LjCIPK16/LjSOS2 module-mediated salt stress signaling in honeysuckle is proposed. This study provides insight into the characteristics of the CBL-CIPK gene families involved in honeysuckle salt stress responses, which could serve as a foundation for gene transformation technology, to obtain highly salt-tolerant medicinal plants in the context of the global reduction of cultivated land.